Pelatihan Pengenalan Excel dalam Pengelolaan Data Administrasi Perkantoran di LKP Pelita Media - Zikra Syah, Arridha; Rizaldi; Maha Putra, Guntur (Akademi Farmasi YPPM Mandiri, 2022)
Microsoft Excel is an office application that is used to model calculations from both the ordinary to the complex ones. LKP Pelita Media provides web and network programming training. LKP Pelita Media provides basic design training for students who have interests and talents in developing information systems. As an option in process analysis which is an important part of requirements analysis, Microsoft Excel can help the system development team. In addition, the participants of LKP Pelita Media are in the upper middle age and early in college. By equipping them with Microsoft excel training, they will be better prepared to face the world of work or higher education. With this training, participants are expected to be able to provide an overview of the management and presentation of good information. The training method is by way of discussion and practice in conveying knowledge of computer introduction and exercises in using excel applications. The assessment of this activity uses a pretest and posttest where participants are able to do the final test well as a measurement of the success of mastering the training with 87% mastery.